Rethinking the concept of crime prevention in the customs sphere - Viktorivna Korotiuk, Oksana; Cherkasskyi, Ruslan Anatolevich; Koniushenko, Yana; Drozd, Valentyna Georgievna (DIXI, 2022)
There is always a tendency in law that there is no way a society can exist without a crime commission, as a society without crime is like a human being without blood. Even though the crime commission has become a common phenomenon in a given society, its reduction and prevention are very imperative for the interest and well-being of the society. Every society that is regulated by a legitimate setup has the responsibility in ensuring the peace and security of this society by taking relevant measures in reducing the rate of crime committed in that society. The problem we face here remains that even though with all the laudable efforts of the various law enforcement agencies and organs in Ukraine, it is still practically difficult and impossible in preventing crime commissions in the country, and there still exists a continuous increase rate of crimes committed in the country. This constant increase in crime commission has provoked a doubt in the mind of many as the customary objective of the society is that of crime prevention. In answering this critical controversy that has surrounded the state of Ukraine as to problem affecting the prevention of crime, it will be proper for us to examine some of those justifications posed that have made it difficult for the State of Ukraine and other law enforcement officials in combating and preventing crimes in the country. It is therefore this backdrop that we think something needs to be done by the State of Ukraine to use all the appropriate measures in ensuring security and social order in the society.
Keywords: legal measures; organizational; social phenomenon; prevention; crime